The Cambridge World History of Food : In Two Volumes - Edited by Kenneth F. Kiple & Kriemhild Conee Ornelas. (Cambridge University Press, 2000)
A history of foods of the world with history of the item, nutrition, where located, etc. Includes plant and animal foods.